Growth Strategy and the Agricultural Sector - Aboyade, Ojentunji (International Food Policy Research Institute, 1987)
An important lesson that experience teaches is that food and agricultural policy cannot be addressed effectively apart from the linkages with the domestic economy and the rest of the world. At lower levels of development, food production and consumption account for sizable portions of national economic activity. Even in a closed economy, food is linked with investment, saving, relative prices, and income distribution. These linkages are even more complex in an open economy, where shifts in external trade, aid, balance of payments, and exchange rates must be considered.